Leaving no one behind: Older African women's rights to sexual and reproductive health - Abubakar, Ibrahim B. (African journal of reproductive health, 2022)
Despite growing agreement on the importance of sexual and reproductive health and rights at all stages of human development, the link between ageing and the sexual and reproductive rights of older African women has been an overlooked topic of research and policy formulation. This commentary takes a multidisciplinary approach to highlighting older African women's sexual and reproductive health and rights, identifying extant legislative frameworks, shortcomings, and strategies to improve their implementation. An examination of the legislative frameworks in place demonstrates that they are insufficient for the full implementation of these rights. As a result, a deliberate effort is required to correct historical wrongs and preserve older women's sexual and reproductive health and rights.